DAMPAK EKOENZIM DAN PROBIOTIK EM4 TERHADAP KUALITAS AIR DAN REPRODUKSI IKAN GUPI - Pratama, Dimas Seno Bagus; Cahyaningrum, Desti Christian; Sucahyo, . (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2024)
Ecoenzyme is considered a potential solution to water quality problems for the guppies aquarium. Ecoenzyme is a multifunctional organic product that people widely use to clean up river water. Ecoenzymes are easy to make because they are mainly vegetable and fruit waste. Based on its function, ecoenzyme has a similar role to EM4 probiotics in maintaining water quality. This study intends to know the effect of various concentrations of eco enzyme on media water quality, survival rate, and reproduction of guppies. The parameters of media water quality measured were pH, temperature, TDS, and ammonia. The research was conducted by giving ecoenzyme concentration treatment of 0, 0.5, 1, 2 mg/L and 0, 0.5, 1, 2 mg/L commercial probiotics for fish as a comparison. The study was conducted for 30 days and then analyzed. The results obtained are the addition of eco enzymes and EM4 probiotics affects the parameters of TDS and DO while the parameters of pH, temperature, ammonia, survival rate, and reproduction of guppies are not affected by it.